A study on student mental health problem during the era of Pandemic COVID-19 in UiTM Seremban 3 / Ahmad Hafiz Saeri and Nur Afiqah Muhamad Fauzi - Saeri, Ahmad Hafiz; Muhamad Fauzi, Nur Afiqah (2022)
In this research, the perspective of student mental health problem during the era of pandemic covid-19 in UiTM Seremban 3 was examined. The factors that affect mental health, students' mental health conditions, and students' academic performance were observed from the results. The purpose of this study is to evaluate the correlation between student academic achievement, factor causes of mental illness, and student mental health status. A total of 200 respondents were sent a survey questionnaire through online using the convenience sampling and quantitative sampling methods. Essentially, those who responded were students at UiTM Seremban 3. All opinions and responses from the participants will be examined using IBM SPSS Statistics 20 in order to investigate how these variables that effect student academic performance. The perspective of factor causes of mental health and student academic performance is positive relationship. for student CGPA and student academic performance, there is no relationship.